EFFECT OF COW BIOURIN POC AND TYPE OF ORGANIC MULCH ON GROWTH AND YIELD OF LONG BEAN (Vigna sinensis L.) - Regita Puspa Rinjani; Abdul Rizal AZ; Darban Haryanto (Jurnal Agrivet, 2021)
This study aims to find out the influence of the dose of liquid organic fertilizer biourin cow and the type of organic mulch is best for the growth and yield of long bean plants. The method used in this study is a Complete Group RandomIzed Design consisting of two factors of 3 x 3 plus 1 control (the use of chemical fertilizers without bovine biourin and organic mulch). The first factor is the dose of liquid organic fertilizer biourin cow (S) consists of 3 levels namely S1 = 400 ml/plant; S2 = 500 ml/plant; S3 = 600 ml/plant. The second factor is the type of organic mulch (M) consists of 3 levels namely M1 = Rice straw; M2 = Reed leaves; M3 = Corn stalk. Plant control is the provision of chemical fertilizers without biourin cows and organic mulch. The data obtained was analyzed using diversity analysis (Anova) at a rate of 5%. To know there is a real difference between control and treatment using Orthgonal Contras test at 5% level, while to know there is a real difference between the treatment then conducted Duncan's Multiple Range Test (DMRT) at the level of 5%.